On-going improvement and persistent differences in the survival for patients with colon and rectum cancer across Europe 1999–2007 – Results from the EUROCARE-5 study. Issue 15 (October 2015) - Holleczek, Bernd; Rossi, Silvia; Domenic, Agius; Innos, Kaire; Minicozzi, Pamela; Francisci, Silvia; Hackl, Monika; Eisemann, Nora; Brenner, Hermann; EUROCARE-5 Working Group, 1
Abstract Background Previous population-based studies revealed major variation in survival for patients with colorectal cancer (CRC) in Europe by age and between different countries and regions, but also a sustained improvement in survival for patients with CRC in recent years. This EUROCARE-5 paper aims to update available knowledge from previous studies and to provide the latest survival estimates for CRC patients from Europe. Methods The study analysed data of patients diagnosed with CRC from population-based cancer registries diagnosed in 29 European countries. Estimates of 1-year and 5-year relative survival (RS) were derived for patients diagnosed in 2000–2007 by European region, country and age at diagnosis. Additionally to these cohort estimates, time trends in 5-year RS were obtained for the calendar periods 1999–2001 and 2005–2007, using the period analysis methodology. Results European average 5-year RS for patients diagnosed with colon and rectum cancer was 57% and 56%, respectively. The analyses showed persistent differences in cancer survival across Europe with lowest survival for CRC patients observed in Eastern Europe. The analyses further showed a strong gradient in age-specific survival. Even though the study revealed sustained improvement in patient survival between 1999–2001 and 2005–2007 (absolute increase of 4 and 6 percentage points for colon and rectum, respectively), the differences in the survival for CRC patients observed at the beginning of the millennium persisted over time. Conclusion Although survival for CRC patients in Europe improved markedly in the study period, significant geographic variations and a strong age gradient still persisted. Enhanced access to effective diagnostic procedures and treatment options might be the keys to reducing the existing disparities in the survival of CRC patients across Europe.